Origin, history and utilization possibilities of Carpathian Braunvieh at Hungary - Békefi, Janka; Gáspárdy, András; Béri, Béla (Acta Agraria Debreceniensis, 2014)
The Carpathian Braunvieh was established by the cross-breeding of Braunvieh and the small dun mountain breeds of the Carpathian basin. It has been breeding in Hungary about 100 years before and still living in Transcarpathia and Transylvania, but only in very mixed populations. Since it was a characteristic native cattle breed of the country, it should be retain for future generations and re-establish in Hungary. Our primary aim is to preserve the breed’s genetic resources and - if appropriate - to acclaim it as an indigenous breed. If there are no longer residuals of the old type Carpathian Braunvieh, it is still worth to preserve as a local variety, because of its many favourable features. Above all, it’s our duty to maintain the breed, because neither Transcarpathia nor Transylvania has a breeding programme for it.